A Study on the Impact of Monetary Policy on Bank Deposits - Ghatak, Anirban (Ushus Journal of Business Management, 2008)
Despite 125 years of capital market experience, 83.9 per cent of households in India still invest only in the safe and sound bank deposits. While only 7.2 per cent of the households were investing in the capital market. Radical transformations had occurred in India’s capital market in the meanwhile